Faire bouger les représentations. Sens et usages d'une métaphore pédagogique - Jean-François Goubet (Nantes Université, 2013)
« Moving representations » is a commonly heard expression in teacher's training world. Two major uses of this expression exist. The first concerns the child, in particular when he or she learns experimental sciences. The second concerns the teacher, who is supposed to wear mourning for some conceptions as he or she begins professionalizing. The sense of the expression, in addition, can be very various. Three meanings are set apart: moving as removing an obstacle, moving as conversing a preconception in a correct idea, moving, at last, as shifting an affect quantum placed on a representation. Certain contemporary French-speaking specialists of experimental sciences didactics appeal to Bachelard. I try to understand what "moving representations" means exactly in different contexts in which Bachelard's name is often evoked.